ChemInform Abstract: AgNa(VO2F2)2: A Trioxovanadium Fluoride with Unconventional Electrochemical Properties. Issue 42 (1st October 2013) - Donakowski, Martin D.; Goerne, Arno; Vaughey, John T.; Poeppelmeier, Kenneth R.
Abstract Crystals and powder of AgNa(VO2F2)2 (I) are prepared by hydrothermal synthesis of a stoichiometric mixture of Ag2O, NaF, and V2O5 in aqueous HF (autoclave, 150 °C, 24 h, 40% yield).